The Metaphor Of Mythology in Henri Fuseli Artworks- Analysis study (Al-Academy, 2025)
The purpose of myth was founded on philosophical questions, and gradually, with the development of philosophical thought, its purpose shifted to explaining social issues, representing its phenomena, and recording rituals, In order to transmit its meaning-laden energy to the recipient through forms of objective reference as an equivalent of the author's ideas about individual events and myths associated with the social events of the present, the title of the research entitled (The metaphor of mythological in Henri Fuseli artworks ) is presented in the form of the first chapter, the methodological framework, and the second chapter with the mythological metaphor in the works of Henri Fuseli. In the first chapter, we identify the role of myth in the Romantic movement, and in the second, we identify the forms of metaphor in Henri Fuseli's paintings, and on the basis of the indicators and sample analysis in the third chapter, we reach the results in the fourth chapter, the most important of which are: - 1- Myth has a psychological impact and its function is to establish ideological foundations as a logical drawing of the phenomena of reality coupled with an illogical drawing of reality dependent on the elements of the myth, as the imagination creates a false consciousness that serves certain political, religious or intellectual purposes. 2- Myth has a psychological function, as it is the drawing of the internal reality and what the incident and the social phenomenon evokes from the artist's emotional reaction. In both cases, it constitutes the author's association with a field of cultural presence based on collective memory, subconscious elements, imagination, dreams, illusions and myths inspired by mythological stories in all their forms.